(untitled) (Iranian Journal of Kidney Diseases, 2014)
Diabetic nephropathy is a major cause of end-stage renal disease throughout the world. Elevated oxidative stress in diabetic patients results from overproduction of reactive oxygen species and decreased efficiency of antioxidant defenses. Moreover, diabetes-associated metabolic disorders impair activities of enzymes of the mitochondrial respiratory chain complex. Therefore, oxidative stress is closely related to mitochondrial dysfunction. This paper reviews studies of mitochondrial dysfunction in diabetic nephropathy.